Pengaruh Kenaikan Pajak Pertambahan Nilai 2025 terhadap Pasar dan Kondisi Sosial Ekonomi Nasional - Patih, Husnama; Rufaedah, Dina Anisya (Journal of Industrial and Syariah Economics, 2025)
Value Added Tax (VAT) has become the primary instrument for increasing state revenue in Indonesia. The policy of increasing the VAT rate from 11% to 12%, as stipulated in the Tax Regulation Harmonization Law, aims to strengthen state revenue, reduce dependence on foreign debt, and align the rate with international standards. However, this VAT rate increase policy raises concerns among the public about its potential impact on market share and socio-economic conditions, inflation, and economic stability, which ultimately affects national income both directly and indirectly. This research aims to analyze the impact of the tax increase on the market and the socio-economic conditions of the nation. The approach used is a literature review method, by examining related literature on VAT in 2025 and relevant economic factors. The analysis shows that an increase in VAT rates can boost state revenue, but may also reduce market share and socio-economic conditions that could trigger inflation, especially in an unstable global situation. In the context of Islamic economics, the application of the principle of ihtisab becomes important to ensure that this policy is implemented fairly and does not harm Indonesian society.